ANALISIS YURIDIS PELAKSANAAN PEMBIAYAAN SYARIAH MUSYARAKAH PADA OCBC-NISP SYARIAH (STUDI KASUS PUTUSAN TINGGI AGAMA NOMOR 128/PDT.G/2022/PTA.MTR): Legal Analysis Of The Implementation Of Musyarakah Islamic Financing At Ocbc-Nisp Syariah (Case Study Of The Religious Court Of Appeal Decision Number 128/Pdt.G/2022/Pta.Mtr) - Kautsar Alwi Pradipta; Siti Nurbaiti (Faculty of Law, Universitas Trisakti, 2025)
In this legal study, the author is interested in examining the implementation of financing with the musyarakah mutanaqisah contract at Bank OCBC NISP Syariah Mataram, which encountered problems between the bank and the debtor. The identified problem in this study is how the musyarakah contract is regulated in Islamic financing, and whether the Decision of the Mataram Religious Court Number 128/Pdt.G/2022/PA.Mtr. is in accordance with Islamic banking regulations. The legal research method used is normative legal research, conducted by collecting primary, secondary, and tertiary legal sources, analyzing data qualitatively, and drawing conclusions using deductive logic. Based on the results and conclusion of the study, it is concluded that Bank OCBC NISP Syariah Mataram must carry out its function as a fund distributor in financing products based on DSN-MUI Fatwa No.05/DSN-MUI/IV/2000, and that Bank OCBC NISP Syariah Mataram was not lawful in executing the auction of mortgage rights over land or a house because it failed to notify the debtor and conducted the execution without a court decision. This study concludes that Bank OCBC NISP Syariah Mataram acted inconsistently with Islamic banking provisions in the execution of mortgage rights against Sigid Wisnu Hernawan as the debtor, as the procedures outlined in Law Number 4 of 1996 on Mortgage Rights were not followed. Moreover, in this case, the panel of judges at the appellate level did not consider the validity of the mortgage execution auction.